THE PLACE OF TRADITIONAL INSTITUTION IN NIGERIA: CHALLENGES, OPPORTUNITIES AND PROSPECTS - HRM Eze Sir Dr. Uzo Nwosu (Global Prosperity, 2022)
The traditional institution in Nigeria is as old as the country. The institution, from the ages, has been the prime instrument through which the various traditional communities are held together, governed and preserved. When the British colonial authorities came into Nigeria at the turn of the 18th Century, they met the traditional institution in the country at varying stages of development. The traditional institution had, by then, become well established in some parts of the country, where they ran centralized political and administrative systems, especially in the Northern and Western parts of the country. In some parts, referred to as acephalous societies, mainly the Eastern parts of Nigeria, the traditional institution came in the form of Village Councils in which the most elderly with a track record of wisdom was put in charge of the affairs of the community. But in the intervening years, especially following the independence of Nigeria in 1960, the traditional institutions have become well emplaced in all parts of the country, the initial flaws that led to its failure in the East, notwithstanding.